NT network programming toolkit - Murphy, John 1959- (Prentice Hall series on Microsoft technologies, 1998)
A practical guide to TCP/IP network programming in an NT environment, this title covers Win 32 File I/O, basic socket concepts, socket operations, and Winsock 1 & 2. The CD-ROM includes a simple telnet server, ftp server, email server, a Web browser and a Web server, and multicast application.